Short cervix detection in pregnant women by transabdominal sonography with post-void technique - Kongwattanakul, Kiattisak; Saksiriwuttho, Piyamas; Komwilaisak, Ratana; Lumbiganon, Pisake (Journal of medical ultrasonics (2001), 2016)
Purpose This study aimed to evaluate the diagnostic properties of transabdominal sonography with the post-void technique for cervical length measurement. Methods This study was a prospective cohort study. The inclusion criteria were pregnant women aged 18–40 years with gestational age of 18–23 completed weeks. Transabdominal sonography with vertical bladder depth of less than 5 cm and transvaginal cervical length measurements were carried out by a single experienced sonographer. Results There were 307 eligible pregnant women. The mean age of all subjects was 29.0 years. The mean cervical length obtained through transabdominal and transvaginal measurement was 3.33 and 3.47 cm, respectively. Ten patients (3.3 %) were identified as having a short cervix using transvaginal sonography, and 12 patients (3.9 %) were identified using transabdominal sonography. Conclusion Transabdominal sonography with vertical bladder depth of less than 5 cm performed better compared with transvaginal sonography. It may not be necessary to perform transvaginal sonography if transabdominal sonography reveals the cervical length to be more than 2.5 cm.